Pendidikan Islam pada Masa Kolonial Belanda: Tantangan, Kebijakan, dan Strategi Bertahan - Amelia Syahvirnawati; Mahfud Ifendi (SETYAKI : Jurnal Studi Keagamaan Islam, 2026)
Islamic education during the Dutch colonial period of 1900–1942 represents an important phase in the development of education in Indonesia. During this period, the colonial government implemented various policies that restricted the development of islamic education through supervision of educational institutions, religious teachers, and learning systems. This study aims to examine the development of islamic education during the Dutch colonial period of 1900–1942, analyze the impact of colonial policies on the implementation of islamic education, and explain the adaptation strategies undertaken by muslim communities in maintaining and developing islamic education under colonial pressure. This study employed a historical research method with a qualitative approach through library research. The data were collected from various written sources, including scientific articles, books on the history of islamic education, documents, and relevant literature related to the development of islamic education during the Dutch colonial period. Data analysis was conducted through historical research stages, including source collection, source criticism, interpretation, and historiography, to understand the relationship between colonial policies, the development of islamic educational institutions, and muslim community responses. The results of the study indicate that despite facing various restrictions imposed by colonial policies, islamic education was able to survive and continue developing. Islamic boarding schools (pesantren), madrasahs, and islamic organizations played significant roles in adapting to colonial challenges through educational reforms, institutional strengthening, and increased community participation. These adaptation strategies became key factors in maintaining the existence of islamic education and contributed to the development of islamic education in Indonesia after independence.